METHODS OF SOLVING OPTIMAL SOLUTIONS OF MATHEMATICAL PROBLEMS WITH ARTIFICIAL INTELLIGENCE METHODS (Modern education and development, 2025)
The article shows that solving mathematical problems can be more effectively implemented using artificial intelligence (AI) than traditional methods. Artificial intelligence, in particular neural networks and deep learning (Deep Learning) methods, significantly simplify and accelerate the process of solving mathematical and statistical problems. This work considers the application, capabilities and practical approaches of artificial intelligence methods in solving mathematical problems.